Aluminum nitride-based conductive ceramic material and preparation method thereof
By adding polycarboxylate long-linked branch carbon nanotubes and ZrB2 to aluminum nitride ceramics, and using ball milling, spray drying, glue discharge, sintering and other processes, the problems of poor conductivity and unstable overall performance of aluminum nitride conductive ceramic materials are solved, and the conductive performance is improved and the performance stability is achieved.
Patent Information
- Application Number
- CN202510215098.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-26
- Publication Date
- 2025-04-15
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing aluminum nitride conductive ceramic materials have poor conductivity and unstable overall performance, resulting in easy damage and short service life.
Aluminum nitride-based conductive ceramic materials are prepared by ball milling, spray drying, glue discharge, sintering and other processes.
It significantly improves the electrical conductivity of aluminum nitride ceramics, while maintaining its good thermal conductivity and mechanical properties, and extending its service life.
Abstract
Description
Technical Field
[0001] The invention relates to the field of aluminum nitride ceramics, and in particular to an aluminum nitride-based conductive ceramic material and a preparation method thereof. Background Art
[0002] Aluminum nitride ceramics are a new type of ceramic material with excellent comprehensive properties. They are ideal materials for the new generation of semiconductor manufacturing and electronic device packaging. They have excellent properties: high thermal conductivity, high electrical insulation, low dielectric constant and loss, non-toxicity, and a thermal expansion coefficient that matches that of silicon. As semiconductor manufacturing, electronic information, and power electronics technology continue to develop in the direction of high integration, high speed, miniaturization, and intelligence, and are widely used in large-scale integrated circuit manufacturing processes, the application and development of aluminum nitride ceramic materials are becoming more and more extensive. However, the electrical insulation of aluminum nitride ceramics limits its application in the field of conduction.
[0003] In recent years, improving the conductivity of aluminum nitride ceramics by adding metal materials as conductive fillers has become a research hotspot. However, the poor interfacial compatibility between metal materials and aluminum nitride matrix leads to unstable conductivity and mechanical properties of aluminum nitride conductive ceramics, which can easily lead to damage and fracture of aluminum nitride conductive ceramics and short service life. Summary of the invention
[0004] In order to overcome the above technical problems, the purpose of the present invention is to provide an aluminum nitride-based conductive ceramic material and a preparation method thereof, which solves the problem that the existing aluminum nitride conductive ceramic has poor conductivity and unstable comprehensive performance.
[0005] The purpose of the present invention can be achieved by the following technical solutions:
[0006] An aluminum nitride-based conductive ceramic material comprises the following components in parts by weight:
[0007] 60-90 parts of aluminum nitride powder, 0.4-1.2 parts of a first reinforcing agent, 3-17 parts of a second reinforcing agent, 2-10 parts of a sintering aid, 1-5 parts of a dispersant, 1-5 parts of a binder, and 80-100 parts of an organic solvent;
[0008] Wherein, the first reinforcing agent is a multi-carboxyl long-chain grafted carbon nanotube;
[0009] Wherein, the second reinforcing agent is any one of ZrB2, TiC, ZrC, TiN, WC and TiB2 or a mixture of any of them in any proportion;
[0010] Wherein, the sintering aid is any one of Y2O3, Al2O3, CaO, Li2O, YF3 and CaF2 or a mixture of any of them in any proportion;
[0011] Wherein, the binder is polyvinyl butyral;
[0012] Wherein, the dispersant is any one of fish oil, castor oil and triolein or a mixture of any of them in any proportion.
[0013] As a further solution of the present invention: the multi-carboxyl long chain grafted carbon nanotubes are prepared by the following steps:
[0014] Step a1: Add carbon nanotubes, concentrated sulfuric acid and concentrated nitric acid into a three-necked flask equipped with a stirrer, a thermometer and an air guide tube, introduce nitrogen protection, stir and react for 20-30 minutes at a temperature of 25-30°C and a stirring rate of 300-400r / min, then heat to 100-110°C and continue stirring and reacting for 20-30 hours. After the reaction is completed, cool the reaction product to room temperature, then vacuum filter, wash the filter cake with distilled water for 3-5 times, then place it in a vacuum drying oven, and dry it at a temperature of 50-55°C for 4-5 hours to obtain pretreated carbon nanotubes;
[0015] Step a2: adding pretreated carbon nanotubes, pentaerythritol, p-toluenesulfonic acid and dimethyl sulfoxide to a three-necked flask equipped with a stirrer, a thermometer and an air guide tube, introducing nitrogen protection, stirring the reaction at a temperature of 25-30°C and a stirring rate of 300-400r / min for 20-30min, then heating to 50-55°C and continuing to stir the reaction for 1-1.5h, then heating to 140-150°C and continuing to stir the reaction for 3-4h, after the reaction is completed, cooling the reaction product to room temperature, then vacuum filtering, washing the filter cake with distilled water and anhydrous ethanol for 3-5 times in turn, then placing it in a vacuum drying oven, and drying it at a temperature of 50-55°C for 4-5h to obtain polyhydroxy-grafted carbon nanotubes;
[0016] Step a3: Add polyhydroxy-grafted carbon nanotubes, sebacic acid, composite catalyst and anhydrous ether into a three-necked flask equipped with a stirrer, a thermometer, an air duct and a reflux condenser, introduce nitrogen protection, stir the reaction for 20-30 minutes at a temperature of 25-30°C and a stirring rate of 300-400r / min, then raise the temperature to reflux and continue stirring the reaction for 20-30 hours. After the reaction is completed, the reaction product is cooled to room temperature, and then vacuum filtered. The filter cake is washed with distilled water for 3-5 times, and then placed in a vacuum drying oven and dried at a temperature of 30-35°C for 6-8 hours to obtain polycarboxyl long-chain grafted carbon nanotubes.
[0017] As a further solution of the present invention: the usage ratio of the carbon nanotubes, concentrated sulfuric acid and concentrated nitric acid in step a1 is 5 g: 60-65 mL: 20-25 mL.
[0018] As a further solution of the present invention: the outer diameter of the carbon nanotubes in step a1 is 30-60 nm, the inner diameter is 20-30 nm, and the length is 1-10 μm; the mass fraction of the concentrated sulfuric acid is 98%; and the mass fraction of the concentrated nitric acid is 67%.
[0019] As a further solution of the present invention: the usage ratio of the pretreated carbon nanotubes, pentaerythritol, p-toluenesulfonic acid and dimethyl sulfoxide in step a2 is 5g: 3-11g: 0.1-0.3g: 100-120mL.
[0020] As a further solution of the present invention: the usage ratio of the polyhydroxy-grafted carbon nanotubes, sebacic acid, composite catalyst and anhydrous ether in step a3 is 5g:4-12g:0.1-0.2g:100-120mL.
[0021] As a further solution of the present invention: the composite catalyst in step a3 is a mixture of tetrabutyl titanate and monobutyl tin oxide in a mass ratio of 1:1-2.
[0022] As a further solution of the present invention: a method for preparing an aluminum nitride-based conductive ceramic material comprises the following steps:
[0023] Step 1, weighing raw materials: weigh 60-90 parts of aluminum nitride powder, 0.4-1.2 parts of the first reinforcing agent, 3-17 parts of the second reinforcing agent, 2-10 parts of the sintering aid, 1-5 parts of the dispersant, 1-5 parts of the binder and 80-100 parts of the organic solvent according to weight parts, and set aside;
[0024] Step 2, mixing and granulating: adding aluminum nitride powder, a first reinforcing agent, a second reinforcing agent, a sintering aid, a dispersant, a binder and an organic solvent into a ball mill, and ball milling for 10-30 hours at a ball milling rate of 300-400 r / min, and then spray drying the mixed slurry obtained by ball milling to obtain aluminum nitride mixture granulated powder with an average particle size of 30-90 μm;
[0025] Step 3: Dry pressing: placing the aluminum nitride mixture granulated powder in a pressure molding machine, and pressing it into a 150×150×8 mm ceramic blank under a pressure of 10-20 MPa;
[0026] Step 4: debinding: placing the ceramic green body in a debinding furnace, and performing debinding treatment under a nitrogen atmosphere at a temperature of 600-800°C to obtain a debinding ceramic green body;
[0027] Step 5, high temperature sintering: placing the debinding ceramic green blank in a high temperature furnace, and sintering it at high temperature for 4-6 hours under a nitrogen atmosphere at a temperature of 1600-1900°C to obtain a eutectic aluminum nitride-based conductive ceramic material;
[0028] Step 6: Crushing: crushing the eutectic aluminum nitride-based conductive ceramic material by a roll crusher or a jaw crusher to obtain a eutectic aluminum nitride-based conductive ceramic powder with an average particle size of 30-90 μm;
[0029] Step 7, secondary dry pressing: placing the eutectic aluminum nitride-based conductive ceramic powder in a pressure molding machine, and pressing it into a conductive ceramic blank of 150×150×8 mm under a pressure of 10-20 MPa;
[0030] Step 8: hot pressing and shaking sintering: placing the conductive ceramic green body in a hot pressing sintering furnace, and sintering it at high temperature for 12-20 hours in a nitrogen atmosphere at a temperature of 1700-1800° C. to obtain an aluminum nitride-based conductive ceramic material.
[0031] Beneficial effects of the present invention:
[0032] The present invention discloses an aluminum nitride-based conductive ceramic material and a preparation method thereof, comprising the steps of ball-milling aluminum nitride powder, a first reinforcing agent, a second reinforcing agent, a sintering aid, a dispersant, a binder and an organic solvent, spray-drying the mixed slurry obtained by ball milling to obtain aluminum nitride mixture granulated powder, pressing the aluminum nitride mixture granulated powder into a ceramic blank, placing the ceramic blank in a debinding furnace for debinding treatment to obtain a debinding ceramic blank, sintering the debinding ceramic blank at high temperature to obtain a eutectic aluminum nitride-based conductive ceramic material, crushing the eutectic aluminum nitride-based conductive ceramic material to obtain a eutectic aluminum nitride-based conductive ceramic powder, and forming the eutectic aluminum nitride-based conductive ceramic. The powder is pressed into a conductive ceramic blank, and the conductive ceramic blank is sintered at a high temperature to obtain an aluminum nitride-based conductive ceramic material. The preparation method uses aluminum nitride powder as the main raw material. Aluminum nitride ceramics have excellent thermal conductivity. After adding the first reinforcing agent and the second reinforcing agent thereto, the resistivity of the aluminum nitride ceramic can be significantly reduced, thereby making it conductive while maintaining its good thermal conductivity and mechanical properties, thereby broadening its application range and being widely used in electronic packaging, thermal management, electromagnetic shielding and other fields, having important market value, and the preparation method is simple and feasible, easy to control, suitable for large-scale industrial production, and in line with the needs of industrialization.
[0033] In the process of preparing aluminum nitride-based conductive ceramic materials, a multi-carboxyl long-chain grafted carbon nanotube is first prepared. First, the carbon nanotube is treated with concentrated sulfuric acid and concentrated nitric acid to remove impurities thereon and introduce a large number of active groups to obtain pretreated carbon nanotubes. Then, the pretreated carbon nanotube is reacted with pentaerythritol, and the carboxyl groups on the pretreated carbon nanotube react with the hydroxyl groups on the pentaerythritol, and a large number of hydroxyl groups are introduced to obtain multi-hydroxy grafted carbon nanotubes. Then, the multi-hydroxy grafted carbon nanotube is reacted with sebacic acid to introduce a large number of carboxyl groups and long carbon chains to obtain multi-hydroxy grafted carbon nanotubes. The multi-hydroxy grafted carbon nanotube is added to the aluminum nitride-based conductive ceramic material as a first enhancer, and the carbon nanotube has excellent electrical conductivity and thermal conductivity. After being dispersed in aluminum nitride-based conductive ceramic materials, they can form smooth conductive networks and thermal conductive networks, which significantly improves the conductive properties of the material while ensuring the thermal conductivity of aluminum nitride ceramics. In addition, during the ball milling process, a large number of carboxyl groups on the polyhydroxy-grafted carbon nanotubes can undergo chemical adsorption with other components, changing the charge distribution on the surface of other components and increasing the electrostatic repulsion between particles. Moreover, the long carbon chain can not only wrap other components but also provide a stronger steric hindrance effect, thereby effectively preventing particle agglomeration and making the material easier to disperse during grinding, thereby improving the interface compatibility between other components and the aluminum nitride matrix, and ultimately making the aluminum nitride-based conductive ceramic material structure dense, further improving its thermal conductivity, electrical conductivity and mechanical properties. DETAILED DESCRIPTION
[0034] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0035] Embodiment 1:
[0036] This embodiment is a method for preparing an aluminum nitride-based conductive ceramic material, comprising the following steps:
[0037] Step S1: 5 g of carbon nanotubes with an outer diameter of 30-60 nm, an inner diameter of 20-30 nm, and a length of 1-10 μm, 60 mL of concentrated sulfuric acid with a mass fraction of 98%, and 20 mL of concentrated nitric acid with a mass fraction of 67% are added to a three-necked flask equipped with a stirrer, a thermometer, and an air guide tube, and nitrogen is introduced for protection. The mixture is stirred for reaction at a temperature of 25° C. and a stirring rate of 300 r / min for 20 min, and then the mixture is heated to 100° C. and stirred for reaction for 20 h. After the reaction is completed, the reaction product is cooled to room temperature, and then vacuum filtered. The filter cake is washed with distilled water for 3 times, and then placed in a vacuum drying oven and dried at a temperature of 50° C. for 4 h to obtain pretreated carbon nanotubes;
[0038] Step S2: 5 g of pretreated carbon nanotubes, 3 g of pentaerythritol, 0.1 g of p-toluenesulfonic acid and 100 mL of dimethyl sulfoxide were added to a three-necked flask equipped with a stirrer, a thermometer and an air duct, and nitrogen was introduced for protection. The mixture was stirred for reaction at a temperature of 25° C. and a stirring rate of 300 r / min for 20 min, and then the mixture was heated to 50° C. and continued to stir for reaction for 1 h, and then heated to 140° C. and continued to stir for reaction for 3 h. After the reaction was completed, the reaction product was cooled to room temperature, and then vacuum filtered. The filter cake was washed three times with distilled water and anhydrous ethanol in sequence, and then placed in a vacuum drying oven and dried at a temperature of 50° C. for 4 h to obtain polyhydroxy-grafted carbon nanotubes;
[0039] Step S3: 5g of a composite catalyst prepared by mixing tetrabutyl titanate and monobutyl tin oxide in a mass ratio of 1:1 and 100mL of anhydrous ether are added to a three-necked flask equipped with a stirrer, a thermometer, an air duct and a reflux condenser, and nitrogen is introduced for protection. The mixture is stirred for reaction at a temperature of 25°C and a stirring rate of 300r / min for 20min, and then the mixture is heated to reflux and stirred for reaction for 20h. After the reaction is completed, the reaction product is cooled to room temperature, and then vacuum filtered. The filter cake is washed with distilled water for 3 times, and then placed in a vacuum drying oven and dried at a temperature of 30°C for 6h to obtain a multi-carboxyl long-chain grafted carbon nanotube.
[0040] Step S4: weigh 60 parts of aluminum nitride powder, 0.4 parts of the first reinforcing agent, 3 parts of the second reinforcing agent, 2 parts of the sintering aid, 1 part of the dispersant, 1 part of the binder and 80 parts of the organic solvent according to weight parts for use; wherein the first reinforcing agent is a multi-carboxyl long-chain grafted carbon nanotube; wherein the second reinforcing agent is ZrB2; wherein the sintering aid is Y2O3; wherein the binder is polyvinyl butyral; wherein the dispersant is fish oil;
[0041] Step S5: adding aluminum nitride powder, a first reinforcing agent, a second reinforcing agent, a sintering aid, a dispersant, a binder and an organic solvent into a ball mill, and ball milling for 10 hours at a ball milling rate of 300 r / min, and then spray drying the mixed slurry obtained by ball milling to obtain aluminum nitride mixture granulated powder with an average particle size of 30-90 μm;
[0042] Step S6: placing the aluminum nitride mixture granulated powder in a pressure molding machine, and pressing it into a ceramic blank of 150×150×8 mm under a pressure of 10 MPa;
[0043] Step S7: placing the ceramic green blank in a binder removal furnace, and performing a binder removal process under a nitrogen atmosphere at a temperature of 600° C. to remove various organic substances in the ceramic green blank, thereby obtaining a binder-free ceramic green blank;
[0044] Step S8: placing the debinding ceramic green blank in a high temperature furnace, and sintering it at a temperature of 1600° C. for 4 hours in a nitrogen atmosphere to obtain a eutectic aluminum nitride-based conductive ceramic material;
[0045] Step S9: crushing the eutectic aluminum nitride-based conductive ceramic material by a roll crusher or a jaw crusher to obtain a eutectic aluminum nitride-based conductive ceramic powder with an average particle size of 30-90 μm;
[0046] Step S10: placing the eutectic aluminum nitride-based conductive ceramic powder in a pressure molding machine, and pressing it into a conductive ceramic blank of 150×150×8 mm under a pressure of 10 MPa;
[0047] Step S11: placing the conductive ceramic green body in a hot pressing sintering furnace, and sintering it at high temperature for 12 hours in a nitrogen atmosphere at a temperature of 1700° C. to obtain an aluminum nitride-based conductive ceramic material.
[0048] Embodiment 2:
[0049] This embodiment is a method for preparing an aluminum nitride-based conductive ceramic material, comprising the following steps:
[0050] Step S1: 5 g of carbon nanotubes with an outer diameter of 30-60 nm, an inner diameter of 20-30 nm, and a length of 1-10 μm, 62 mL of concentrated sulfuric acid with a mass fraction of 98%, and 22 mL of concentrated nitric acid with a mass fraction of 67% are added to a three-necked flask equipped with a stirrer, a thermometer, and an air guide tube, and nitrogen is introduced for protection. The mixture is stirred for reaction at a temperature of 28° C. and a stirring rate of 350 r / min for 25 min, and then the temperature is raised to 105° C. and the stirring reaction is continued for 25 h. After the reaction is completed, the reaction product is cooled to room temperature, and then vacuum filtered. The filter cake is washed with distilled water 4 times, and then placed in a vacuum drying oven and dried at a temperature of 52° C. for 4.5 h to obtain pretreated carbon nanotubes;
[0051] Step S2: 5 g of pretreated carbon nanotubes, 7 g of pentaerythritol, 0.2 g of p-toluenesulfonic acid and 110 mL of dimethyl sulfoxide were added to a three-necked flask equipped with a stirrer, a thermometer and an air duct, and nitrogen was introduced for protection. The mixture was stirred for reaction at a temperature of 28° C. and a stirring rate of 350 r / min for 25 min, and then the mixture was heated to 52° C. and continued to stir for reaction for 1 h, and then the mixture was heated to 145° C. and continued to stir for reaction for 3.5 h. After the reaction was completed, the reaction product was cooled to room temperature, and then vacuum filtered. The filter cake was washed with distilled water and anhydrous ethanol for 4 times in sequence, and then placed in a vacuum drying oven and dried at a temperature of 52° C. for 4.5 h to obtain polyhydroxy-grafted carbon nanotubes;
[0052] Step S3: 5g of a composite catalyst prepared by mixing tetrabutyl titanate and monobutyl tin oxide in a mass ratio of 1:1.5 and 110mL of anhydrous ether were added to a three-necked flask equipped with a stirrer, a thermometer, an air duct and a reflux condenser, and nitrogen was introduced for protection. The mixture was stirred for reaction at a temperature of 28°C and a stirring rate of 350r / min for 25min, and then the mixture was heated to reflux and continued to stir for 25h. After the reaction was completed, the reaction product was cooled to room temperature, and then vacuum filtered. The filter cake was washed with distilled water 4 times, and then placed in a vacuum drying oven and dried at a temperature of 32°C for 7h to obtain a multi-carboxyl long-chain grafted carbon nanotube.
[0053] Step S4: 75 parts of aluminum nitride powder, 0.8 parts of a first reinforcing agent, 10 parts of a second reinforcing agent, 6 parts of a sintering aid, 3 parts of a dispersant, 3 parts of a binder and 90 parts of an organic solvent are weighed in parts by weight for later use; wherein the first reinforcing agent is a multi-carboxyl long-chain grafted carbon nanotube; wherein the second reinforcing agent is TiN; wherein the sintering aid is Al2O3; wherein the binder is polyvinyl butyral; wherein the dispersant is castor oil;
[0054] Step S5: adding aluminum nitride powder, a first reinforcing agent, a second reinforcing agent, a sintering aid, a dispersant, a binder and an organic solvent into a ball mill, and ball milling for 20 hours at a ball milling rate of 350 r / min, and then spray drying the mixed slurry obtained by ball milling to obtain aluminum nitride mixture granulated powder with an average particle size of 30-90 μm;
[0055] Step S6: placing the aluminum nitride mixture granulated powder in a pressure molding machine, and pressing it into a ceramic blank of 150×150×8 mm under a pressure of 15 MPa;
[0056] Step S7: placing the ceramic green blank in a binder removal furnace, and performing a binder removal process under a nitrogen atmosphere at a temperature of 700° C. to remove various organic matters in the ceramic green blank, thereby obtaining a binder-free ceramic green blank;
[0057] Step S8: placing the debinding ceramic green blank in a high temperature furnace, and sintering it at a temperature of 1750° C. for 5 hours in a nitrogen atmosphere to obtain a eutectic aluminum nitride-based conductive ceramic material;
[0058] Step S9: crushing the eutectic aluminum nitride-based conductive ceramic material by a roll crusher or a jaw crusher to obtain a eutectic aluminum nitride-based conductive ceramic powder with an average particle size of 30-90 μm;
[0059] Step S10: placing the eutectic aluminum nitride-based conductive ceramic powder in a pressure molding machine, and pressing it into a conductive ceramic blank of 150×150×8 mm under a pressure of 15 MPa;
[0060] Step S11: placing the conductive ceramic green body in a hot pressing sintering furnace, and sintering it at high temperature for 16 hours in a nitrogen atmosphere at a temperature of 1750° C. to obtain an aluminum nitride-based conductive ceramic material.
[0061] Embodiment 3:
[0062] This embodiment is a method for preparing an aluminum nitride-based conductive ceramic material, comprising the following steps:
[0063] Step S1: 5 g of carbon nanotubes with an outer diameter of 30-60 nm, an inner diameter of 20-30 nm, and a length of 1-10 μm, 65 mL of concentrated sulfuric acid with a mass fraction of 98%, and 25 mL of concentrated nitric acid with a mass fraction of 67% are added to a three-necked flask equipped with a stirrer, a thermometer, and an air guide tube, and nitrogen is introduced for protection. The mixture is stirred for reaction at a temperature of 30° C. and a stirring rate of 400 r / min for 30 min, and then the temperature is raised to 110° C. and the stirring reaction is continued for 30 h. After the reaction is completed, the reaction product is cooled to room temperature, and then vacuum filtered. The filter cake is washed with distilled water for 5 times, and then placed in a vacuum drying oven and dried at a temperature of 55° C. for 5 h to obtain pretreated carbon nanotubes;
[0064] Step S2: 5 g of pretreated carbon nanotubes, 11 g of pentaerythritol, 0.3 g of p-toluenesulfonic acid and 120 mL of dimethyl sulfoxide were added to a three-necked flask equipped with a stirrer, a thermometer and an air duct, and nitrogen was introduced for protection. The mixture was stirred for reaction at a temperature of 30° C. and a stirring rate of 400 r / min for 30 min, and then the mixture was heated to 55° C. and continued to stir for reaction for 1.5 h, and then the mixture was heated to 150° C. and continued to stir for reaction for 4 h. After the reaction, the reaction product was cooled to room temperature, and then vacuum filtered. The filter cake was washed with distilled water and anhydrous ethanol for 5 times in sequence, and then placed in a vacuum drying oven and dried at a temperature of 55° C. for 5 h to obtain polyhydroxy-grafted carbon nanotubes;
[0065] Step S3: 5g of a composite catalyst prepared by mixing tetrabutyl titanate and monobutyl tin oxide in a mass ratio of 1:2 and 120mL of anhydrous ether are added to a three-necked flask equipped with a stirrer, a thermometer, an air duct and a reflux condenser, and nitrogen is introduced for protection. The mixture is stirred for reaction at a temperature of 30°C and a stirring rate of 400r / min for 30min, and then the mixture is heated to reflux and stirred for reaction for 30h. After the reaction is completed, the reaction product is cooled to room temperature, and then vacuum filtered. The filter cake is washed with distilled water for 5 times, and then placed in a vacuum drying oven and dried at a temperature of 35°C for 8h to obtain a multi-carboxyl long-chain grafted carbon nanotube.
[0066] Step S4: weigh 90 parts of aluminum nitride powder, 1.2 parts of a first reinforcing agent, 17 parts of a second reinforcing agent, 10 parts of a sintering aid, 5 parts of a dispersant, 5 parts of a binder and 100 parts of an organic solvent in parts by weight for later use; wherein the first reinforcing agent is a multi-carboxyl long-chain grafted carbon nanotube; wherein the second reinforcing agent is TiB2; wherein the sintering aid is Li2O; wherein the binder is polyvinyl butyral; wherein the dispersant is triolein;
[0067] Step S5: adding aluminum nitride powder, a first reinforcing agent, a second reinforcing agent, a sintering aid, a dispersant, a binder and an organic solvent into a ball mill, and ball milling for 30 hours at a ball milling rate of 400 r / min, and then spray drying the mixed slurry obtained by ball milling to obtain aluminum nitride mixture granulated powder with an average particle size of 30-90 μm;
[0068] Step S6: placing the aluminum nitride mixture granulated powder in a pressure molding machine, and pressing it into a ceramic blank of 150×150×8 mm under a pressure of 20 MPa;
[0069] Step S7: placing the ceramic green blank in a binder removal furnace, and performing a binder removal process under a nitrogen atmosphere at a temperature of 800° C. to remove various organic substances in the ceramic green blank, thereby obtaining a binder-free ceramic green blank;
[0070] Step S8: placing the debinding ceramic green blank in a high temperature furnace, and sintering it at a temperature of 1900° C. for 6 hours in a nitrogen atmosphere to obtain a eutectic aluminum nitride-based conductive ceramic material;
[0071] Step S9: crushing the eutectic aluminum nitride-based conductive ceramic material by a roll crusher or a jaw crusher to obtain a eutectic aluminum nitride-based conductive ceramic powder with an average particle size of 30-90 μm;
[0072] Step S10: placing the eutectic aluminum nitride-based conductive ceramic powder in a pressure molding machine, and pressing it into a conductive ceramic blank of 150×150×8 mm under a pressure of 20 MPa;
[0073] Step S11: placing the conductive ceramic green body in a hot pressing sintering furnace, and sintering it at high temperature for 20 hours in a nitrogen atmosphere at a temperature of 1800° C. to obtain an aluminum nitride-based conductive ceramic material.
[0074] Comparative Example 1:
[0075] This comparative example is a method for preparing an aluminum nitride-based conductive ceramic material, comprising the following steps:
[0076] Step S1: weighing 90 parts of aluminum nitride powder, 10 parts of sintering aid, 5 parts of dispersant, 5 parts of binder and 100 parts of organic solvent according to weight parts for standby use; wherein the sintering aid is Li2O; wherein the binder is polyvinyl butyral; wherein the dispersant is triolein;
[0077] Step S2: adding aluminum nitride powder, sintering aid, dispersant, binder and organic solvent into a ball mill, and ball milling for 30 hours at a ball milling rate of 400 r / min, and then spray drying the mixed slurry obtained by ball milling to obtain aluminum nitride mixture granulated powder with an average particle size of 30-90 μm;
[0078] Step S3: placing the aluminum nitride mixture granulated powder in a pressure molding machine, and pressing it into a ceramic blank of 150×150×8 mm under a pressure of 20 MPa;
[0079] Step S4: placing the ceramic green blank in a binder removal furnace, and performing a binder removal process under a nitrogen atmosphere at a temperature of 800° C. to remove various organic matters in the ceramic green blank, thereby obtaining a binder-free ceramic green blank;
[0080] Step S5: placing the debinding ceramic green blank in a high temperature furnace, and sintering it at high temperature for 6 hours in a nitrogen atmosphere at a temperature of 1900° C. to obtain a eutectic aluminum nitride-based conductive ceramic material;
[0081] Step S6: crushing the eutectic aluminum nitride-based conductive ceramic material by a roll crusher or a jaw crusher to obtain a eutectic aluminum nitride-based conductive ceramic powder with an average particle size of 30-90 μm;
[0082] Step S7: placing the eutectic aluminum nitride-based conductive ceramic powder in a pressure molding machine, and pressing it into a conductive ceramic blank of 150×150×8 mm under a pressure of 20 MPa;
[0083] Step S8: placing the conductive ceramic green body in a hot pressing sintering furnace, and sintering it at high temperature for 20 hours in a nitrogen atmosphere at a temperature of 1800° C. to obtain an aluminum nitride-based conductive ceramic material.
[0084] Comparative Example 2:
[0085] This comparative example is a method for preparing an aluminum nitride-based conductive ceramic material, comprising the following steps:
[0086] Step S1: weigh 90 parts of aluminum nitride powder, 17 parts of a second reinforcing agent, 10 parts of a sintering aid, 5 parts of a dispersant, 5 parts of a binder and 100 parts of an organic solvent according to weight parts for standby use; wherein the second reinforcing agent is TiB2; wherein the sintering aid is Li2O; wherein the binder is polyvinyl butyral; wherein the dispersant is triolein;
[0087] Step S2: adding aluminum nitride powder, a second reinforcing agent, a sintering aid, a dispersant, a binder and an organic solvent into a ball mill, and ball milling for 30 hours at a ball milling rate of 400 r / min, and then spray drying the mixed slurry obtained by ball milling to obtain aluminum nitride mixture granulated powder with an average particle size of 30-90 μm;
[0088] Step S3: placing the aluminum nitride mixture granulated powder in a pressure molding machine, and pressing it into a ceramic blank of 150×150×8 mm under a pressure of 20 MPa;
[0089] Step S4: placing the ceramic green blank in a binder removal furnace, and performing a binder removal process under a nitrogen atmosphere at a temperature of 800° C. to remove various organic matters in the ceramic green blank, thereby obtaining a binder-free ceramic green blank;
[0090] Step S5: placing the debinding ceramic green blank in a high temperature furnace, and sintering it at high temperature for 6 hours in a nitrogen atmosphere at a temperature of 1900° C. to obtain a eutectic aluminum nitride-based conductive ceramic material;
[0091] Step S6: crushing the eutectic aluminum nitride-based conductive ceramic material by a roll crusher or a jaw crusher to obtain a eutectic aluminum nitride-based conductive ceramic powder with an average particle size of 30-90 μm;
[0092] Step S7: placing the eutectic aluminum nitride-based conductive ceramic powder in a pressure molding machine, and pressing it into a conductive ceramic blank of 150×150×8 mm under a pressure of 20 MPa;
[0093] Step S8: placing the conductive ceramic green body in a hot pressing sintering furnace, and sintering it at high temperature for 20 hours in a nitrogen atmosphere at a temperature of 1800° C. to obtain an aluminum nitride-based conductive ceramic material.
[0094] Comparative Example 3:
[0095] This comparative example is a method for preparing an aluminum nitride-based conductive ceramic material, comprising the following steps:
[0096] Step S1: 5 g of carbon nanotubes with an outer diameter of 30-60 nm, an inner diameter of 20-30 nm, and a length of 1-10 μm, 65 mL of concentrated sulfuric acid with a mass fraction of 98%, and 25 mL of concentrated nitric acid with a mass fraction of 67% are added to a three-necked flask equipped with a stirrer, a thermometer, and an air guide tube, and nitrogen is introduced for protection. The mixture is stirred for reaction at a temperature of 30° C. and a stirring rate of 400 r / min for 30 min, and then the temperature is raised to 110° C. and the stirring reaction is continued for 30 h. After the reaction is completed, the reaction product is cooled to room temperature, and then vacuum filtered. The filter cake is washed with distilled water for 5 times, and then placed in a vacuum drying oven and dried at a temperature of 55° C. for 5 h to obtain pretreated carbon nanotubes;
[0097] Step S2: 5 g of pretreated carbon nanotubes, 11 g of pentaerythritol, 0.3 g of p-toluenesulfonic acid and 120 mL of dimethyl sulfoxide were added to a three-necked flask equipped with a stirrer, a thermometer and an air duct, and nitrogen was introduced for protection. The mixture was stirred for reaction at a temperature of 30° C. and a stirring rate of 400 r / min for 30 min, and then the mixture was heated to 55° C. and continued to stir for reaction for 1.5 h, and then the mixture was heated to 150° C. and continued to stir for reaction for 4 h. After the reaction, the reaction product was cooled to room temperature, and then vacuum filtered. The filter cake was washed with distilled water and anhydrous ethanol for 5 times in sequence, and then placed in a vacuum drying oven and dried at a temperature of 55° C. for 5 h to obtain polyhydroxy-grafted carbon nanotubes;
[0098] Step S3: 5g of a composite catalyst prepared by mixing tetrabutyl titanate and monobutyl tin oxide in a mass ratio of 1:2 and 120mL of anhydrous ether are added to a three-necked flask equipped with a stirrer, a thermometer, an air duct and a reflux condenser, and nitrogen is introduced for protection. The mixture is stirred for reaction at a temperature of 30°C and a stirring rate of 400r / min for 30min, and then the mixture is heated to reflux and stirred for reaction for 30h. After the reaction is completed, the reaction product is cooled to room temperature, and then vacuum filtered. The filter cake is washed with distilled water for 5 times, and then placed in a vacuum drying oven and dried at a temperature of 35°C for 8h to obtain a multi-carboxyl long-chain grafted carbon nanotube.
[0099] Step S4: weighing 90 parts of aluminum nitride powder, 1.2 parts of a first reinforcing agent, 10 parts of a sintering aid, 5 parts of a dispersant, 5 parts of a binder and 100 parts of an organic solvent according to weight parts for standby use; wherein the first reinforcing agent is a multi-carboxyl long-chain grafted carbon nanotube; wherein the sintering aid is Li2O; wherein the binder is polyvinyl butyral; wherein the dispersant is triolein;
[0100] Step S5: adding aluminum nitride powder, a first reinforcing agent, a sintering aid, a dispersant, a binder and an organic solvent into a ball mill, and ball milling for 30 hours at a ball milling rate of 400 r / min, and then spray drying the mixed slurry obtained by ball milling to obtain aluminum nitride mixture granulated powder with an average particle size of 30-90 μm;
[0101] Step S6: placing the aluminum nitride mixture granulated powder in a pressure molding machine, and pressing it into a ceramic blank of 150×150×8 mm under a pressure of 20 MPa;
[0102] Step S7: placing the ceramic green blank in a binder removal furnace, and performing a binder removal process under a nitrogen atmosphere at a temperature of 800° C. to remove various organic substances in the ceramic green blank, thereby obtaining a binder-free ceramic green blank;
[0103] Step S8: placing the debinding ceramic green blank in a high temperature furnace, and sintering it at a temperature of 1900° C. for 6 hours in a nitrogen atmosphere to obtain a eutectic aluminum nitride-based conductive ceramic material;
[0104] Step S9: crushing the eutectic aluminum nitride-based conductive ceramic material by a roll crusher or a jaw crusher to obtain a eutectic aluminum nitride-based conductive ceramic powder with an average particle size of 30-90 μm;
[0105] Step S10: placing the eutectic aluminum nitride-based conductive ceramic powder in a pressure molding machine, and pressing it into a conductive ceramic blank of 150×150×8 mm under a pressure of 20 MPa;
[0106] Step S11: placing the conductive ceramic green body in a hot pressing sintering furnace, and sintering it at high temperature for 20 hours in a nitrogen atmosphere at a temperature of 1800° C. to obtain an aluminum nitride-based conductive ceramic material.
[0107] Comparative Example 4:
[0108] This comparative example is a method for preparing an aluminum nitride-based conductive ceramic material, comprising the following steps:
[0109] Step S1: weigh 90 parts of aluminum nitride powder, 1.2 parts of a first reinforcing agent, 17 parts of a second reinforcing agent, 10 parts of a sintering aid, 5 parts of a dispersant, 5 parts of a binder and 100 parts of an organic solvent according to weight parts for later use; wherein the first reinforcing agent is a carbon nanotube with an outer diameter of 30-60nm, an inner diameter of 20-30nm and a length of 1-10μm; wherein the second reinforcing agent is TiB2; wherein the sintering aid is Li2O; wherein the binder is polyvinyl butyral; wherein the dispersant is triolein;
[0110] Step S2: adding aluminum nitride powder, a first reinforcing agent, a second reinforcing agent, a sintering aid, a dispersant, a binder and an organic solvent into a ball mill, and ball milling for 30 hours at a ball milling rate of 400 r / min, and then spray drying the mixed slurry obtained by ball milling to obtain aluminum nitride mixture granulated powder with an average particle size of 30-90 μm;
[0111] Step S3: placing the aluminum nitride mixture granulated powder in a pressure molding machine, and pressing it into a ceramic blank of 150×150×8 mm under a pressure of 20 MPa;
[0112] Step S4: placing the ceramic green blank in a binder removal furnace, and performing a binder removal process under a nitrogen atmosphere at a temperature of 800° C. to remove various organic matters in the ceramic green blank, thereby obtaining a binder-free ceramic green blank;
[0113] Step S5: placing the debinding ceramic green blank in a high temperature furnace, and sintering it at high temperature for 6 hours in a nitrogen atmosphere at a temperature of 1900° C. to obtain a eutectic aluminum nitride-based conductive ceramic material;
[0114] Step S6: crushing the eutectic aluminum nitride-based conductive ceramic material by a roll crusher or a jaw crusher to obtain a eutectic aluminum nitride-based conductive ceramic powder with an average particle size of 30-90 μm;
[0115] Step S7: placing the eutectic aluminum nitride-based conductive ceramic powder in a pressure molding machine, and pressing it into a conductive ceramic blank of 150×150×8 mm under a pressure of 20 MPa;
[0116] Step S8: placing the conductive ceramic green body in a hot pressing sintering furnace, and sintering it at high temperature for 20 hours in a nitrogen atmosphere at a temperature of 1800° C. to obtain an aluminum nitride-based conductive ceramic material.
[0117] Comparative Example 5:
[0118] This comparative example is a method for preparing an aluminum nitride-based conductive ceramic material, comprising the following steps:
[0119] Step S1: 5 g of carbon nanotubes with an outer diameter of 30-60 nm, an inner diameter of 20-30 nm, and a length of 1-10 μm, 65 mL of concentrated sulfuric acid with a mass fraction of 98%, and 25 mL of concentrated nitric acid with a mass fraction of 67% are added to a three-necked flask equipped with a stirrer, a thermometer, and an air guide tube, and nitrogen is introduced for protection. The mixture is stirred for reaction at a temperature of 30° C. and a stirring rate of 400 r / min for 30 min, and then the temperature is raised to 110° C. and the stirring reaction is continued for 30 h. After the reaction is completed, the reaction product is cooled to room temperature, and then vacuum filtered. The filter cake is washed with distilled water for 5 times, and then placed in a vacuum drying oven and dried at a temperature of 55° C. for 5 h to obtain pretreated carbon nanotubes;
[0120] Step S2: 5 g of pretreated carbon nanotubes, 11 g of pentaerythritol, 0.3 g of p-toluenesulfonic acid and 120 mL of dimethyl sulfoxide were added to a three-necked flask equipped with a stirrer, a thermometer and an air duct, and nitrogen was introduced for protection. The mixture was stirred for reaction at a temperature of 30° C. and a stirring rate of 400 r / min for 30 min, and then the mixture was heated to 55° C. and continued to stir for reaction for 1.5 h, and then the mixture was heated to 150° C. and continued to stir for reaction for 4 h. After the reaction, the reaction product was cooled to room temperature, and then vacuum filtered. The filter cake was washed with distilled water and anhydrous ethanol for 5 times in sequence, and then placed in a vacuum drying oven and dried at a temperature of 55° C. for 5 h to obtain polyhydroxy-grafted carbon nanotubes;
[0121] Step S3: weigh 90 parts of aluminum nitride powder, 1.2 parts of a first reinforcing agent, 17 parts of a second reinforcing agent, 10 parts of a sintering aid, 5 parts of a dispersant, 5 parts of a binder and 100 parts of an organic solvent in parts by weight for later use; wherein the first reinforcing agent is polyhydroxy-grafted carbon nanotubes; wherein the second reinforcing agent is TiB2; wherein the sintering aid is Li2O; wherein the binder is polyvinyl butyral; wherein the dispersant is triolein;
[0122] Step S4: adding aluminum nitride powder, a first reinforcing agent, a second reinforcing agent, a sintering aid, a dispersant, a binder and an organic solvent into a ball mill, and ball milling for 30 hours at a ball milling rate of 400 r / min, and then spray drying the mixed slurry obtained by ball milling to obtain aluminum nitride mixture granulated powder with an average particle size of 30-90 μm;
[0123] Step S5: placing the aluminum nitride mixture granulated powder in a pressure molding machine, and pressing it into a ceramic blank of 150×150×8 mm under a pressure of 20 MPa;
[0124] Step S6: placing the ceramic green blank in a binder removal furnace, and performing a binder removal process under a nitrogen atmosphere at a temperature of 800° C. to remove various organic substances in the ceramic green blank, thereby obtaining a binder-free ceramic green blank;
[0125] Step S7: placing the debinding ceramic green blank in a high temperature furnace, and sintering it at a temperature of 1900° C. for 6 hours in a nitrogen atmosphere to obtain a eutectic aluminum nitride-based conductive ceramic material;
[0126] Step S8: crushing the eutectic aluminum nitride-based conductive ceramic material by a roll crusher or a jaw crusher to obtain a eutectic aluminum nitride-based conductive ceramic powder with an average particle size of 30-90 μm;
[0127] Step S9: placing the eutectic aluminum nitride-based conductive ceramic powder in a pressure molding machine, and pressing it into a conductive ceramic blank of 150×150×8 mm under a pressure of 20 MPa;
[0128] Step S10: placing the conductive ceramic green body in a hot pressing sintering furnace, and sintering it at high temperature for 20 hours in a nitrogen atmosphere at a temperature of 1800° C. to obtain an aluminum nitride-based conductive ceramic material.
[0129] The aluminum nitride-based conductive ceramic materials of Examples 1-3 and Comparative Examples 1-5 were subjected to resistivity tests on a high-precision DC low resistance tester. The test results are shown in the following table:
[0130] sample <![CDATA[Bulk density, g / cm 3 > Resistivity, Ω·cm Example 1 6.21 <![CDATA[6.31×10 -4 ]]> Example 2 6.38 <![CDATA[5.17×10 -4 ]]> Example 3 6.55 <![CDATA[4.09×10 -4 ]]> Comparative Example 1 3.35 <![CDATA[3.26×10 14 ]]> Comparative Example 2 3.16 <![CDATA[2.39×10 -1 ]]> Comparative Example 3 5.84 <![CDATA[5.34×10 -2 ]]> Comparative Example 4 3.08 <![CDATA[8.12×10 -3 ]]> Comparative Example 5 4.72 <![CDATA[2.08×10 -3 ]]>
[0131] Referring to the data in the above table, based on the comparison between Examples 1-3 and Comparative Examples 1-5, it can be known that the aluminum nitride-based conductive ceramic material of the present invention has excellent conductive properties.
[0132] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0133] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined in this application, they shall all fall within the protection scope of the present invention.
Claims
1. An aluminum nitride-based conductive ceramic material, characterized in that: It comprises the following components in parts by weight: 60-90 parts of aluminum nitride powder, 0.4-1.2 parts of a first reinforcing agent, 3-17 parts of a second reinforcing agent, 2-10 parts of a sintering aid, 1-5 parts of a dispersant, 1-5 parts of a binder, and 80-100 parts of an organic solvent; Wherein, the first reinforcing agent is a multi-carboxyl long-chain grafted carbon nanotube; Wherein, the second reinforcing agent is any one of ZrB2, TiC, ZrC, TiN, WC and TiB2 or a mixture of any of them in any proportion; Wherein, the sintering aid is any one of Y2O3, Al2O3, CaO, Li2O, YF3 and CaF2 or a mixture of any of them in any proportion; Wherein, the binder is polyvinyl butyral; Wherein, the dispersant is any one of fish oil, castor oil and triolein or a mixture of any of them in any proportion.
2. The aluminum nitride-based conductive ceramic material according to claim 1, characterized in that: The multi-carboxyl long chain grafted carbon nanotubes are prepared by the following steps: Step a1: stirring carbon nanotubes, concentrated sulfuric acid and concentrated nitric acid to react, cooling the reaction product after the reaction is completed, and then vacuum filtering, washing and drying the filter cake to obtain pretreated carbon nanotubes; Step a2: stirring the pretreated carbon nanotubes, pentaerythritol, p-toluenesulfonic acid and dimethyl sulfoxide to react, cooling the reaction product after the reaction is completed, and then vacuum filtering, washing and drying the filter cake to obtain polyhydroxy-grafted carbon nanotubes; Step a3: stirring the polyhydroxy-grafted carbon nanotubes, sebacic acid, composite catalyst and anhydrous ether for reaction, cooling the reaction product after the reaction is completed, and then vacuum filtering, washing and drying the filter cake to obtain polycarboxyl long-chain grafted carbon nanotubes.
3. The aluminum nitride-based conductive ceramic material according to claim 2, characterized in that: The usage ratio of the carbon nanotubes, concentrated sulfuric acid and concentrated nitric acid in step a1 is 5 g: 60-65 mL: 20-25 mL.
4. The aluminum nitride-based conductive ceramic material according to claim 2, characterized in that: The carbon nanotubes in step a1 have an outer diameter of 30-60 nm, an inner diameter of 20-30 nm, and a length of 1-10 μm; the mass fraction of the concentrated sulfuric acid is 98%; and the mass fraction of the concentrated nitric acid is 67%.
5. The aluminum nitride-based conductive ceramic material according to claim 2, characterized in that: The usage ratio of the pretreated carbon nanotubes, pentaerythritol, p-toluenesulfonic acid and dimethyl sulfoxide in step a2 is 5g: 3-11g: 0.1-0.3g: 100-120mL.
6. The aluminum nitride-based conductive ceramic material according to claim 2, characterized in that: The usage ratio of the polyhydroxy-grafted carbon nanotubes, sebacic acid, composite catalyst and anhydrous ether in step a3 is 5g:4-12g:0.1-0.2g:100-120mL.
7. The aluminum nitride-based conductive ceramic material according to claim 2, characterized in that: The composite catalyst in step a3 is a mixture of tetrabutyl titanate and monobutyl tin oxide in a mass ratio of 1:1-2.
8. A method for preparing an aluminum nitride-based conductive ceramic material according to any one of claims 1 to 7, characterized in that: The following steps are involved: Step 1, weighing raw materials: weigh 60-90 parts of aluminum nitride powder, 0.4-1.2 parts of the first reinforcing agent, 3-17 parts of the second reinforcing agent, 2-10 parts of the sintering aid, 1-5 parts of the dispersant, 1-5 parts of the binder and 80-100 parts of the organic solvent according to weight parts, and set aside; Step 2, mixing and granulating: adding aluminum nitride powder, a first reinforcing agent, a second reinforcing agent, a sintering aid, a dispersant, a binder and an organic solvent into a ball mill, and ball milling for 10-30 hours at a ball milling rate of 300-400 r / min, and then spray drying the mixed slurry obtained by ball milling to obtain aluminum nitride mixture granulated powder with an average particle size of 30-90 μm; Step 3: dry pressing: placing the aluminum nitride mixture granulated powder in a pressure molding machine, and pressing it into a 150×150×8 mm ceramic blank under a pressure of 10-20 MPa; Step 4: debinding: placing the ceramic green body in a debinding furnace, and performing debinding treatment under a nitrogen atmosphere at a temperature of 600-800°C to obtain a debinding ceramic green body; Step 5, high temperature sintering: placing the debinding ceramic green blank in a high temperature furnace, and sintering it at high temperature for 4-6 hours under a nitrogen atmosphere at a temperature of 1600-1900°C to obtain a eutectic aluminum nitride-based conductive ceramic material; Step 6: Crushing: crushing the eutectic aluminum nitride-based conductive ceramic material by a roll crusher or a jaw crusher to obtain a eutectic aluminum nitride-based conductive ceramic powder with an average particle size of 30-90 μm; Step 7, secondary dry pressing: placing the eutectic aluminum nitride-based conductive ceramic powder in a pressure molding machine, and pressing it into a conductive ceramic blank of 150×150×8 mm under a pressure of 10-20 MPa; Step 8: Hot pressing and shaking sintering: Place the conductive ceramic green body in a hot pressing sintering furnace, and perform high temperature sintering for 12-20 hours in a nitrogen atmosphere at a temperature of 1700-1800° C. to obtain an aluminum nitride-based conductive ceramic material.
Citation Information
Patent Citations
Method for preparing high water soluble Nano carbon tube grafted by super branched polymer
CN101092739A
Preparation method of aluminum nitride base microwave-absorbing ceramic
CN101643353A
Carbon nanofiber reinforced aluminum nitride composite ceramic and preparation method thereof
CN101935220A
Aluminum nitride-based conductive ceramic and preparation method thereof
CN115677353A
Multi-carboxyl polymer grafted water-soluble carbon nanometer tube and preparation method thereof
CN1546545A